Pengaruh Berbagai Media Tanam Berbasis Limbah Kelapa Sawit terhadap Pertumbuhan Bibit Kelapa Sawit (Elaeis guineensis jacg) Pre Nursery - lucky handy ardiansyah; Siti Asmaniyah Mardiyani; Anis Sholihah (Universitas Islam Malang, 2023)
Oil palm (Elaeis guineensis Jacg.) is the top row of the largest plantation commodities and benefits from various things such as supporting the country's foreign exchange and also absorbing labor. This study aims to determine the effect of various planting media based on palm waste on the growth of pre nursery oil palm seedlings. This study used a simple randomized block design, consisting of 5 treatments which were repeated 3 times and each replicate contained 3 plant samples to obtain 45 polybags of plant samples. Observational data for each parameter were analyzed using the ANOVA test with a significant level of 5%. If there is a significant effect between the treatments, a further test will be carried out with a level of 5%. Parameters observed were plant height, stem diameter, number of leaves, leaf area, total fresh weight of roots, total dry weight of roots, and dry weight of roots. The results showed that the T3 treatment gave better results on the variable growth parameters: plant height 20.57 cm, stem diameter 7.53 mm, number of leaves 4.56 and leaf area 122.15 cm2 at 12 WAP observations. The results showed that the T3 treatment gave better results on the variable parameter observations total fresh weight of 11.09 grams, fresh root weight of 3.89 grams, total dry weight of 3.62 grams and root dry weight of 1.18 grams.